2008
DOI: 10.1002/ajmg.b.30745
|View full text |Cite
|
Sign up to set email alerts
|

Family based association study of pediatric bipolar disorder and the dopamine transporter gene (SLC6A3)

Abstract: The dopamine transporter gene (SLC6A3) is a compelling candidate for pediatric bipolar disorder because (a) it has been associated with ADHD, (b) bipolar comorbidity with ADHD has been hypothesized to be an etiologically distinct familial subtype (c) blockade of the dopamine transporter with psychostimulants can induce mania in susceptible individuals and (d) previous studies have implicated the gene in bipolar disorder in adults. We conducted a family-based association study of SLC6A3 in 170 affected offsprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 44 publications
1
38
1
1
Order By: Relevance
“…The impact of the rs40184 polymorphism on the susceptibility of MDD is of immense interest since it has been recently shown to be associated with specific neuropsychiatric and neurological disorders (Haeffel et al, 2008;Zhou et al, 2008;Mick et al, 2008;Todt et al, 2009). Although the molecular connection between this SNP and cellular DAT1 level has not been demonstrated, many reports in the literature link polymorphisms of unknown function to certain psychiatric diseases (Cook Jr. et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of the rs40184 polymorphism on the susceptibility of MDD is of immense interest since it has been recently shown to be associated with specific neuropsychiatric and neurological disorders (Haeffel et al, 2008;Zhou et al, 2008;Mick et al, 2008;Todt et al, 2009). Although the molecular connection between this SNP and cellular DAT1 level has not been demonstrated, many reports in the literature link polymorphisms of unknown function to certain psychiatric diseases (Cook Jr. et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This particular SNP has also been found to play a genetic role in certain neuropsychiatric and neurological illnesses such as attention deficit hyperactivity disorder (Zhou et al, 2008), bipolar disorder (Mick et al, 2008) and migraine with aura (Todt et al, 2009). With regard to the genotyping technologies used in the research findings addressed above, the rs40184 polymorphism was genotyped on one of the high-throughput platforms, particularly Sequenom, Taqman and Illumina.…”
Section: Introductionmentioning
confidence: 99%
“…A lower cerebral basal dopamine concentration in patients with the mutant genotype of the SLC6A3 gene could diminish the risk for delirium. The other SNP of interest in the SLC6A3 gene rs40184 is associated with bipolar disorder and conduct disorder in children, which shows some overlapping symptoms with delirium [Mick et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Given the central role of dopamine in regulation of mood and behaviour, it's not surprising that several studies have evidenced that DAT1 is the major candidate gene in the pathogenesis of externalizing problems in childhood. In particular, genetic association studies have linked DAT1 gene to ADHD (Fernandez-Jaen et al 2015;Sokolova et al 2015;Thissen et al 2015, Giana et al, 2015, conduct disorder (Lahey et al, 2011), and pediatric bipolar disorder (Mick et al, 2008). Regarding genetic variants of DAT1, the pioneering study of Cook et al, (1995) have reported a significant association between ADHD and the 10-repeat allele of DAT1.…”
Section: Dopamine Transportermentioning
confidence: 99%